INTERACTION OF SCHOOLCHILDREN WITH NATURE AS A SOCIO-PEDAGOGICAL PROBLEM - I.H. Lyubar (Academy of Cognitive and Natural Sciences, 2022)
In clause the guestion on interaction of the school boys with a nature rises as racially pedagogical problem.